O contributo dos métodos qualitativos na investigação em contabilidade de gestão - Silva, Rui (2013)
This paper presents the contribution more and more important of qualitative methodologies and paradigms associated with them for the development of research in accounting. The work allows demonstrating the importance of qualitative research methods through its use in three family businesses seeking the best way to transfer the management between generations. The study presents advantages and disadvantages of qualitative methods in case studies and contributes to the literature by applying and verifying the effectiveness of the methods in cases of companies with common characteristics, but with totally different dimensions and activities.